ChemInform Abstract: Polythiophene and Oligothiophene Systems Modified by TTF Electroactive Units for Organic Electronics. Issue 12 (March 2016) - Kanibolotsky, Alexander L.; Findlay, Neil J.; Skabara, Peter J.
Abstract: Review: [87 refs.